An Asymptomatic Pulmonary Arteriovenous Malformation Case Mimicking a Cavitary Lung Lesion - Vardaloğlu, Ilgım; Çalışkaner Öztürk, Buket; Durmaz, Emine Şebnem; Bilgiç, Seçkin; Börekçi, Şermin (Cerrahpaşa Medical Journal, 2022)
Cavitary lung lesions can be seen due to tuberculosis, malignancy, and rheumatological diseases. Pulmonary arteriovenous malformations are rare lesions that may contain cavitation. Our case is a pulmonary arteriovenous malformation encountered in a patient with rheumatoid arthritis who is receiving immunosuppressive therapy. Cite this article as: Vardaloğlu I, Çalışkaner Öztürk B, Durmaz EŞ, Bilgiç S, Börekçi S. An asymptomatic pulmonary arteriovenous malformation case mimicking a cavitary lung lesion. Cerrahpaşa Med J. 2022;46(3):272-274.